Synthesis, Anti-Bacterial and Anti-Fungal Evaluation of Pyrazoline Derivatives - Ashvin D. Panchal; Pravinkumar M. Patel (E-Journal of Chemistry)
The Series of N-(5-(Substituted phenyl)-4,5-dihydro-1H-pyrazol-3-yl)-4H-1,2,4-triazol-4-amine compounds were prepared by reaction of 4-amino-1,2,4-Triazole with Acetyl Chloride followed by different aromatic aldehydes and cyclization with hydrazine hydrate. The structures of new compounds were confirmed by IR and 1H-NMR spectral data. Anti-bacterial and Anti-fungal activities were evaluated and compared with the standard drugs, some compounds of the series exhibited promising anti-microbial and anti-fungal activity compared to standard drugs.